Study of the variation of the leading edge of a railway crane on the aerodynamic characteristics - Willy Hardi Vernando; Andre Kurniawan; Randi Purnama Putra; Mirta Widia (Researcher and Lecturer Society, 2024)
The front body design of the railway crane is flat or bluff type. The design causes a large drag, so the railway crane requires high fuel consumption to drive. Therefore, this study aims to modify the front body of the railway crane by applying the shape of the leading edge to reduce drag. This research also investigates the effect of leading-edge angles on aerodynamic characteristics. The method used is computational fluid dynamics, using the flow simulation feature of the Solidworks research licence software. This study considered three variations of leading edge angle (40°, 45° and 50°). The simulation results show that the larger the leading edge angle, the lower the drag coefficient value. In addition, the simulation shows that there is a high air pressure at the front of the railway crane with the bluff shape, while the modified railway crane with the leading edge applied has a lower air pressure at the front. Furthermore, the results and discussion in this article present the simulation results showing the velocity streamline and pressure contour of each model.